2014
DOI: 10.3390/ijerph110909082
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Sport and “Cardiac Injury”: A Prospective Study of Recreational Ironman Athletes

Abstract: Background: Participation in triathlon competitions has increased in recent years. Many studies have described left or right ventricular injury in endurance athletes. The goal of this study was to examine the right and left ventricular cardiac structures and function and dynamic cardio-pulmonary performance in a large cohort of middle- and long-distance triathletes. Methods: 87 triathletes (54 male and 33 female) were examined using spiroergometry and echocardiography. The inclusion criterion was participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 72 publications
(106 reference statements)
3
33
0
5
Order By: Relevance
“…The discrepancy to a recently published study by Breuckmann et al 11 showing myocardial LGE in 12% of healthy male marathon runners (n=102) aged 50 to 72 years and 4% in the age-matched control group could be explained by the selection of participants in our trial (age range, 30-50 years; no history of cardiac disease; no competitive sports), which is in accordance to Karlstedt et al 32 LV and RV ejection fraction in our study did not alter with training. This finding corresponds to results of previous echocardiographic 33 and CMR imaging studies 34 that showed that even dramatic changes in training loads do not influence this index of integrated ventricular systolic function at rest. Therefore, we conclude that the increase in stroke volume in the HI(I)T group is attributable to the larger EDV of hypertrophied ventricles, despite higher endsystolic volume.…”
supporting
confidence: 80%
“…The discrepancy to a recently published study by Breuckmann et al 11 showing myocardial LGE in 12% of healthy male marathon runners (n=102) aged 50 to 72 years and 4% in the age-matched control group could be explained by the selection of participants in our trial (age range, 30-50 years; no history of cardiac disease; no competitive sports), which is in accordance to Karlstedt et al 32 LV and RV ejection fraction in our study did not alter with training. This finding corresponds to results of previous echocardiographic 33 and CMR imaging studies 34 that showed that even dramatic changes in training loads do not influence this index of integrated ventricular systolic function at rest. Therefore, we conclude that the increase in stroke volume in the HI(I)T group is attributable to the larger EDV of hypertrophied ventricles, despite higher endsystolic volume.…”
supporting
confidence: 80%
“…It is well established in sport physiology that endurance training may improve exercise capacity and cardiac function at rest and during exercise. 5,17 Echocardiographic examinations of all cyclists showed that LVH subjects had an increase in LVMI (p < 0.001), as well as, higher LVPWT (p < 0.05) and IVSDD (p < 0.05). Similar differences were observed in the mass of the left ventricular in other endurance athletes.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 That is why the world's sporting and cardiology organizations recommend that medical examinations be performed on competitive endurance athletes for the early detection of possible pathologies. 4,5 Strenuous exercise, such as road cycling, may result in compensatory myocardial hypertrophy, commonly known as athlete's heart. 6 The main morphologic characteristics are left ventricular hypertrophy (LVH), an increase in the coronary reserve and improvement of left ventricular myocardial contractility.…”
mentioning
confidence: 99%
“…Eine Echokardiographie erfolgt hauptsächlich, um die Größe der Kammern/Vorhöfe zu vergleichen und eventuelle Veränderungen im Bereich der Herzklappen und der Aorta zu erfassen [65]. Eine Aortenerweiterung [65] mit konsekutiver Aortenklappeninsuffizienz ist bei Ausdauersportlern nicht selten (2%) [39]. Bei ambitionierten und Wettkampfsportlern erfolgt außerhalb der WettkampfSaison oft eine Spiroergometrie, um die Trainingsplanung zu über-prüfen; bei Leistungssportlern auch in der Vor-Wettkampfphase.…”
Section: Allgemeine Kontrollen ▼unclassified
“…Die Diagnostik mittels Spiroergometrie ist extrem wichtig bei der Trainingsplanung und der Leistungsbeurteilung bei aktiven Sportlern [39] sowie bei der Aktivitätsplanung der betroffenen Patienten [30]. Nur die Spiroergometrie liefert in der Gesamtheit der Daten eine optimale Beurteilung des Sportlers/des Patienten bezüglich der Fettverbrennung, der Trainingsbereiche und der Leistungseinschätzung.…”
Section: Leistungsdiagnostikunclassified